Novel methodology for determining the effect of adsorbates on human enamel acid dissolution. (January 2018) - Pechlivani, N.; Devine, D.A.; Marsh, P.D.; Mighell, A.; Brookes, S.J.
Highlights: Method for investigating effect of adsorbates on acid dissolution of enamel. Effect of repeated acid exposures on adsorbates can be measured over time. Specific salivary proteins significantly reduced acid demineralisation of enamel. Desorption of specific proteins corresponds to reduction in protection against acid. Abstract: Objective: The effect of various interventions on enamel demineralisation can be determined by chemically measuring mineral ions dissolved by the attacking acid. Results are usually expressed as mineral loss per surface area of enamel exposed. Acid resistant varnish or adhesive tape are typically used to delineate an area of enamel. However, enamel surface curvature, rugosity and porosity reduce the reliability of simple area measurements made at the macro scale. Our aim was to develop a simple method for investigating the effect of adsorbates on enamel demineralisation that does not rely on knowing the area of enamel exposed. As an exemplar we have used salivary proteins as a model adsorbate. Design: Natural human tooth enamel surfaces were subjected to five sequential acid challenges and then incubated in adsorbate (whole clarified saliva) followed by a further 15 acid challenges. Demineralisation was determined by measuring the phosphate released into the acid during each exposure by a spectrophotometric assay. The initial five challenges established a mean baseline mineral loss for each tooth against which the effect of subsequently adsorbed proteins could be compared. Results: Salivary proteins significantly reduced the acid demineralisation of human enamel by 43% (p < 0.01). Loss of proteins during each challenge corresponded to a gradual reduction in the degree of protection afforded. Conclusions: The methodology provides a simple and flexible means to investigate the effect of any adsorbate on enamel acid dissolution. Knowledge of the area of exposed enamel is irrelevant as each tooth acts as its own negative control.